Réponses

Meilleure réponse !
2012-12-12T21:14:26+01:00

A = 49y² +56y+16 + 81y² -54y+9 (identité remarquable)

= 130y² +2y +25

 

B = 9y²-81y -(49y² +28y+4)

= 9y²-81y-49y²-28y-4

= -40y² -109y -4

 

c = (15y²-35y-18y+42) - (25y²+30y -30y-36)

= 15y² - 53y+42-25y²+36

= -10y²-53y +78

2012-12-12T21:26:34+01:00

A=((7y)²+2X7yX4 +4²)+((9y)²-2X9yX3+3²

 =49y²+56y+16+81-54y+9

 =49y²+2y+106

 

 

B=9y(y-9)-(7y+2)²

  =(9yXy-9yX9)-((7y)²+2X7yX2+2²)

 = 9y²-81y-(49y²+28y+4)

=9y²-81y-49y²-28y-4

=40y²-109y-4